Performance of the soil biological indicators in dairy units - Rodr?guez, Idalmis; Crespo, Gustavo; Morales, A.; Calero, B.; Fraga, F. (Cuban Journal of Agricultural Science, 2011)
Six cattle production units were selected to evaluate the soil biological indicators. They were located in the San Jos? de las Lajas municipality, in the Mayabeque province. The following conditions were considered: soil type, grasslands, and management systems. Different indicators of the microflora activity (basal respiration and induced by different substrates and cellulolytic activity), and the macro and the mesofauna were studied. The microbial biomass activity had little differences between the units. The magnitudes of the basal respiration in the soils were high (0.85-1.18 mg CO2. g soil-1). All the soils responded to the addition of carbon, nitrogen, and phosphorus. From the point of view of the microbiological quality, the units four and five had the best conditions. There were mesofauna populations in the different grassland agroecosystems. The population dynamics of these groups could not be predicted in the sampling months. The number of acari and collembolans was determined as compared with other insects. In the soil macrofauna, there were differences (P < 0.001) as to the number of individuals and the biomass between the two strata under study in all the units, except the one and the four. The units three, four, and five showed superior values, between 2.5 and 2.33 individuals m-2. However, the one (14 de Valle del Per?) and two (Gen?tico 4), with smaller populations, had superior biomass values. The earthworms, the Coleoptera larvae, and the ants were the main groups in the ecosystems under study. The soils did not show signs of microbiological degradation and there was presence of the rest of the edaphic soil groups (meso and macrofauna). It was concluded that the biological indicators were appropriate in all the units under study. Further study is recommended, at long term, as well as making new studies with cultural practices that stimulate the species diversity in the grasslands. Key words: biological indicators, microflora, mesofauna, macrofauna.